Naddy’s Cookies / Nur Amirah Nadhirah Rusman and Siti Nur Nadzirah Kamal Azmin - Rusman, Nur Amirah Nadhirah; Kamal Azmin, Siti Nur Nadzirah (2022)
The requirement to construct Facebook business pages for the launch of our new company, Naddy's Cookies, led to the creation of this report. The names of the business's founders, Nur Amirah Nadhirah and Siti Nur Nadzirah, were also used in choosing the name of the company. In general, Naddy's Cookies is a company that sells sweet food like chocolate. We want to create chocolate-based snacks by emulating the tastes and trends of today's youth. When this company first started, we solely offered quality chocolate-flavored chocojar. We vary the kinds of toppings available to enhance the flavors of the chocojar as a draw. Our business is homemade based. This indicates that chocojar is only made at home using components that are easily found in supermarkets. We can create high-quality, not overly sweet chocolate that is suited for all ages with a capital of RM50. The cost of the product is very reasonable; a jar of a bottle weighing about 250g costs RM 12 with promotion RM10. Nowadays, a lot of individuals enjoy using the app to buy their needs and wants. This evidence is growing even as the COVID-19 epidemic continues to spread across our nation. We are also active users of social media as a venue for product promotion. Considering Facebook has a larger user base than other social media, we decided to use it. Facebook has also offered a specific platform for conducting business. Automatic ad promotion, turning on notifications for each post made, and post types are some of the features. We presented a teaser, a hard sale, and a soft sell on this Facebook page.